Role of M1 macrophages in diabetic foot ulcers and related immune regulatory mechanisms - Li, Yao; Li, Xiaoyan; Ju, Shuai; Li, Wenqiang; Zhou, Siyuan; Wang, Guili; Cai, Yunmin; Dong, Zhihui (Frontiers in Pharmacology, 2023)
Objectives Diabetes foot ulcer (DFUs) characterized of immune infiltration of M1 macrophages observed in foot skin, in which immune-associated genes (IRGs) play a prominent role; IRG's precise expression as well as any possible regulatory mechanisms that could be present in DFUs are yet unknown. Methods The analysis of the sequencing data of single cell RNA (scRNA) in foot skin of patients with DFUs was carried out, with the cluster marker genes of foot skin obtained from the ImmPort database screened out. IRG activity was assessed with AUCell software package. The IRGs of DFUs were explored by analyzing the batch sequencing data set of DFUs skin tissue. Human TFDB database was adopted to identify the relevant regulatory transcription factors (TFs). The STRING dataset was used to build the main TF's protein-protein interaction networks. Finally, WB and immunofluorescence methods were used to verify M1 macrophage-related immune regulators. Results There were 16 clusters found, such as SMC1, fibro, t-lympho, he fibro, vasendo, baselkera, diffkera, SMC2, M1 macro, M2 macro, sweet/seba, B-Lympho, Melanio, lymphendo, plasma and Schwann. M1 & M2 macrophages both had considerably higher AUC ratings than patients with DFUs compared to other sub-populations of cells. The proportion of M1 macrophages reached the highest in the non-healing group. According to analysis of scRNA and batch sequencing data by go and KEGG, DEGs were enriched in immune response. 106 M1 macroirgs were finally identified. 25 transcription factors were revealed associated with IRG expression. PPI network indicated the NFE2L2, REL, ETV6, MAF and NFIB as central transcription factors. Conclusions Based on the bio-informatics analysis of scRNA and high-throughput sequencing data, we concluded that M1 macrophages may serve as the influencing factor of DFUs nonunion. In addition, NFE2L2 could be involved in the regulation of IRG expression within M1 macrophages.